Dental caries, age and anxiety: factors influencing sedation choice for children attending for emergency dental care - Carson P, Freeman R (Blackwell Synergy, 2001)
The aim of the study was to examine how physical (dental caries) and psychosocial (age, dental anxiety and dental health behaviour) factors, associated with child and parent, influenced dentists’ sedation choice when a child presents in pain. Methods: 600 parents whose children were aged between 5 and 11 years took part: 200 attended for routine dental care (RDC); the remaining 400 attended as emergency patients and were offered either dental general anaesthesia (DGA) or relative analgesia (RA). The subjects were approached and invited to take part.